Assessment of sternal closure using titanium plate - Arnoni,Renato Tambellini (2013)
INTRODUCTION: The use of plates and screws for more rigid fixation of the sternum, without maintaining contact between the upper portion of the sternum and mediastinum. The present study seeks new choice of plate with a significant difference, the same does not need to be removed in order to proceed to open when necessary sternal emerging opening of the bone. OBJECTIVE: The current study aims to evaluate the efficacy and safety of this procedure. METHODS: To this end, we selected ten patients with coronary artery disease have shown no significant risk factors for mediastinitis. The surgery was thus performed in the usual way that all patients with coronary artery disease surgeries are done at the institution. Only at the time of sternal closure is that there was a change, with the combination of steel wires and plates. RESULTS: All cases had sternal closure properly with good outcome in the medium term. CONCLUSION: The use of plates ENGIMPLAN proved safe and effective for sternal closure.